Distinct prognostic values and potential drug targets of ALDH1 isoenzymes in non-small-cell lung cancer - You Q; Guo H; Xu D (Dove Medical Press, 2015)
Qinghua You,1 Huanchen Guo,2 Dongxiang Xu3 1Department of Pathology, Shanghai Pudong Hospital, Fudan University Pudong Medical Center, Shanghai, 2Department of Respiratory Medicine, Shouguang Hospital of Traditional Chinese Medicine, Shouguang, 3Department of Endocrinology, Shanghai Pudong Hospital, Fudan University Pudong Medical Center, Shanghai, People’s Republic of China Abstract: Increased aldehyde dehydrogenase 1 (ALDH1) activity has been found in the stem cell populations of leukemia and some solid tumors including non-small-cell lung cancer (NSCLC). However, which ALDH1’s isoenzymes are contributing to ALDH1 activity remains elusive. In addition, the prognostic value of individual ALDH1 isoenzyme is not clear. In the current study, we investigated the prognostic value of ALDH1 isoenzymes in NSCLC patients through the Kaplan–Meier plotter database, which contains updated gene expression data and survival information from a total of 1,926 NSCLC patients. High expression of ALDH1A1 mRNA was found to be correlated to a better overall survival (OS) in all NSCLC patients followed for 20 years (hazard ratio [HR] 0.88 [0.77–0.99], P=0.039). In addition, high expression of ALDH1A1 mRNA was also found to be correlated to better OS in adenocarcinoma (Ade) patients (HR 0.71 [0.57–0.9], P=0.0044) but not in squamous cell carcinoma (SCC) patients (HR 0.92 [0.72–1.16], P=0.48). High expression of ALDH1A2 and ALDH1B1 mRNA was found to be correlated to worser OS in all NSCLC patients, as well as in Ade, but not in SCC patients. High expression of both ALDH1A3 and ALDH1L1 mRNA was not found to be correlated to OS in all NSCLC patients. These results strongly support that ALDH1A1 mRNA in NSCLC is associated with better prognosis. In addition, our current study also supports that ALDH1A2 and ALDH1B1 might be major contributors to the ALDH1 activity in NSCLC, since high expression of ALDH1A2 and ALDH1B1 mRNA was found to be significantly correlated to worser OS in all NSCLC patients. Based on our study, ALDH1A2 and ALDH1B1 might be excellent potential drug targets for NSCLC patients. Keywords: NSCLC, ALDH1, cancer stem cell, prognosis, drug target, KM plotter, hazard ratio